Preparation method and application of zif-67 composite sodium lignosulfonate hydrogel catalyst
Patent Information
- Application Number
- CN202410062034.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-16
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-01-16
AI Technical Summary
但是ZIF-67在水处理中存在的易流失和团聚等问题,限制了其工业应用
(1)本发明的ZIF-67@SL催化剂的制备工艺简单、易操作,反应条件温和,直接在水相进行反应,有效避免使用有毒有害的有机溶剂,同时降低了能量的消耗,是一种绿色环保的制备工艺。
Smart Images

Figure CN118106033B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of environmental catalytic materials technology, and in particular to a method for preparing and applying a ZIF-67 composite sodium lignosulfonate hydrogel catalyst. Background Technology
[0002] With the continuous exploitation and development of unconventional oilfields, a large amount of oily wastewater is inevitably generated, containing high concentrations of toxic and harmful organic pollutants such as phenols, polycyclic aromatic hydrocarbons (PAHs), and benzene compounds. PAHs, as persistent organic pollutants, are characterized by their stable structure, high toxicity, and ability to accumulate and persist in organisms for extended periods. Untreated PAHs, if discharged indiscriminately, will inevitably cause serious environmental pollution. Advanced oxidation technologies that generate sulfate radicals have attracted significant research attention due to their ability to efficiently, thoroughly, and non-selectively mineralize pollutants, while also offering a wider pH range compared to the widely used Fenton process and a longer half-life than hydroxyl radicals. The method of activating persulfate with heterogeneous transition metal catalysts to generate sulfate radicals offers advantages such as simple operation, cost-effectiveness, and the ability to be reused multiple times.
[0003] ZIF-67, a zeolite imidazole ester framework material, exhibits highly efficient catalytic performance. This material is composed of Co... 2+ ZIF-67, synthesized by coordination with 2-methylimidazole, possesses advantages such as high specific surface area and porosity, and abundant active sites, making it widely used in catalysis, adsorption, and water treatment. For example, Hou et al. demonstrated good degradation effects of tetracycline using hydrogen peroxide activated with synthesized ZIF-67; Hou et al. also showed excellent results in purifying As(III) in water using ZIF-67 / S(Ⅳ) coupled oxidation and adsorption. However, problems such as easy loss and aggregation of ZIF-67 in water treatment limit its industrial application. Summary of the Invention
[0004] This invention provides a method for preparing and applying a ZIF-67 composite sodium lignosulfonate hydrogel catalyst. By combining ZIF-67 with sodium lignosulfonate hydrogel, not only can the problems of easy loss and agglomeration be solved, but the catalytic performance can also be improved.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: a method for preparing a ZIF-67 composite sodium lignosulfonate hydrogel catalyst (ZIF-67@SL), comprising the following steps: S1. Add the aqueous solution of 2-methylimidazole dropwise to the aqueous solution of cobalt ions and mix well, then add the deprotonating agent and mix well. S2. Add the monomer acrylamide (AM), the crosslinking agent N,N'-methylenebisacrylamide (MBA), and sodium lignosulfonate (SL) to the mixed solution obtained in S1, and preheat and stir until homogeneous; S3. Add potassium persulfate (KPS) to the mixture obtained in S2, mix well and react, then wash and dry to obtain ZIF-67 composite sodium lignosulfonate hydrogel catalyst.
[0006] Furthermore, the amount of cobalt ions added to the cobalt ion aqueous solution of S1 is 0.10~0.20 mmol / mL; the molar ratio of cobalt ions to 2-methylimidazole is 1:2~32.
[0007] Furthermore, the cobalt ions are derived from any one of cobalt acetate, cobalt sulfate, cobalt chloride, and cobalt nitrate.
[0008] Further, the deprotonating agent is ammonia (NH3·H2O) or triethylamine (TEA), and the amount added is 4.0%~20% (v / v) of the mixed solution.
[0009] Furthermore, the amount of monomer added in S2 is 40~60 mg / mL, the amount of crosslinking agent added is 2.1~2.7 mg / mL, and the amount of sodium lignosulfonate added is 2.5~10 mg / mL.
[0010] Furthermore, the preheating temperature in S2 is 35-50 ℃.
[0011] Furthermore, the amount of potassium persulfate added in S3 is 5.0 mg / mL to 11.5 mg / mL.
[0012] Furthermore, the reaction time in S3 is 3-10 min, the temperature is 40-50℃, and after the reaction is completed, it is washed with deionized water and anhydrous ethanol, and finally dried under vacuum at 60℃ to obtain the final product.
[0013] The present invention also relates to the ZIF-67 composite sodium lignin sulfonate hydrogel catalyst prepared by the method described above.
[0014] The present invention also relates to the application of the ZIF-67 composite sodium lignosulfonate hydrogel catalyst in the catalytic degradation of polycyclic aromatic hydrocarbons (PAHs) by activated potassium persulfate (PMS).
[0015] The present invention has the following beneficial effects: (1) The preparation process of the ZIF-67@SL catalyst of the present invention is simple and easy to operate. The reaction conditions are mild and the reaction is carried out directly in the aqueous phase, which effectively avoids the use of toxic and harmful organic solvents and reduces energy consumption. It is a green and environmentally friendly preparation process.
[0016] (2) One of the raw materials for the hydrogel prepared by the method disclosed in this invention is lignin sulfonate from industrial pulping waste liquid. It is widely available, non-toxic, inexpensive and readily available, and has good biocompatibility. The hydrogel prepared by using inexpensive, readily available and environmentally friendly sodium lignin sulfonate as a carrier to load ZIF-67 has good flexibility and stability, which facilitates the recycling and reuse of the catalyst. The ZIF-67 modified by sodium lignin sulfonate hydrogel has increased hydrophilicity and dispersibility. In addition, the addition of ZIF-67 and sodium lignin sulfonate improves the mechanical properties, swelling properties, permeability and specific surface area of the hydrogel. The addition of sodium lignin sulfonate is also beneficial to increase the loading of ZIF-67 on cement adhesive.
[0017] (3) The ZIF-67@SL catalyst prepared by the method disclosed in this invention has good catalytic performance and can effectively catalyze the removal of polycyclic aromatic hydrocarbons by PMS, and has good application prospects. Attached Figure Description
[0018] Figure 1 Synthetic route diagram for ZIF-67 composite sodium lignosulfonate hydrogel catalyst.
[0019] Figure 2 The infrared spectrum of the ZIF-67 composite sodium lignosulfonate hydrogel catalyst prepared in Example 1 is shown.
[0020] Figure 3 The images show the physical and FESEM images of the ZIF-67 composite sodium lignosulfonate hydrogel catalyst prepared in Example 1.
[0021] Figure 4 This is a low-magnification EDS-mapping observation of the ZIF-67 composite sodium lignosulfonate hydrogel catalyst prepared in Example 1.
[0022] Figure 5 The image shows the effect of the ZIF-67 composite sodium lignosulfonate hydrogel catalyst prepared in Example 1 on the catalytic removal of naphthalene by different oxidants.
[0023] Figure 6 The image shows the effect of the catalyst prepared in Example 1 on the removal of naphthalene in different systems.
[0024] Figure 7 This is a graph showing the factors influencing the catalytic performance of ZIF-67@SL in Example 7.
[0025] Figure 8 The XRD patterns are of the products prepared using different deprotonating agents in Example 8.
[0026] Figure 9The images show SEM images of products prepared using different deprotonating agents in Example 8, where (a) 1:2 NH3·H2O; (b) 1:4 NH3·H2O; (c) 1:2 TEA; and (d) 1:4 TEA. Detailed Implementation
[0027] The embodiments of the present invention will now be described in detail with reference to examples.
[0028] Example 1 A method for preparing a ZIF-67@SL catalyst, the synthetic route is as follows: Figure 1 This includes the following steps: (1) Weigh 28.8 mmol of 2-methylimidazole and add it dropwise to 7.2 mmol of cobalt ion solution (cobalt nitrate) while stirring continuously; the concentration of 2-methylimidazole is 2.88 mmol / mL and the concentration of cobalt ion solution is 0.72 mmol / mL. (2) Then add 12.5% (V / V) of the deprotonating agent triethylamine (TEA) to the mixed solution, stir at room temperature for 30 min, and let stand for 24 h; (3) Add 2.032 g of monomer acrylamide (AM), 0.0976 g of crosslinking agent MBA and 0.4 mg of sodium lignosulfonate (SL) to the above suspension, seal the beaker, preheat and stir in a constant temperature water bath to dissolve, and then sonicate for 20 min to disperse the suspension evenly. (4) Add 0.4 mg of initiator persulfate (KPS) to the above mixture, shake quickly, place in a mold, and carry out free radical polymerization reaction in a constant temperature water bath at 45 °C. After a period of time, ZIF-67 composite sodium lignosulfonate hydrogel catalyst is obtained.
[0029] (5) Finally, the product is washed with deionized water and anhydrous ethanol several times. After washing, it is vacuum dried at 60 °C to constant weight to obtain ZIF-67 composite sodium lignosulfonate hydrogel catalyst (ZIF-67@SL).
[0030] Figure 2 This is the infrared spectrum of the ZIF-67 composite sodium lignosulfonate hydrogel catalyst. Figure 2 It can be seen that lignin hydrogels at 1600 cm⁻¹ -1 and 1400 cm -1 The absorption at this point is caused by the stretching vibrations of the aromatic ring skeleton (C=C) in the structure; 1120cm -1 Caused by COC stretching vibration; at 1650 cm- 1The absorption peak at 3162 cm⁻¹ is caused by the stretching vibration of the -C=O group in the -CONH₂ group of the grafted acrylamide (AM). The absorption vibration in ZIF-67 mainly originates from Hmim. −1 The absorption peak originates from the NH stretching vibration of the imidazole ring; while the 1415 cm⁻¹ peak... −1 Stretching vibrations from CN bonds; 1350–1500 cm -1 1000~1350 cm -1 These are attributed to the stretching vibration and in-plane bending vibration of the imidazole ring, respectively; 757 cm⁻¹, 693 cm⁻¹ -1 Caused by the outward bending vibration of the imidazole ring. 426 cm -1 The absorption peak at that location is attributed to Co-N. The presence of Co-N, CN, etc. in the ZIF-67@SL composite material indicates that ZIF-67 was successfully loaded into the lignin hydrogel.
[0031] See the physical image of the catalyst. Figure 3 (a) The basic appearance of ZIF-67@SL remains intact, exhibiting an overall bright purple cube-like structure. Detailed morphological and microstructural observations of ZIF-67@SL were performed using FESEM, as detailed in [see attached image]. Figure 3 (b)~(d) reveal that the ZIF-67@SL surface exhibits a loose and porous structure. Furthermore, well-dispersed ZIF-67 particles loaded onto the hydrogel can be observed, indicating that the lignin hydrogel, as a carrier, can provide numerous attachment sites. Observations were performed using low-magnification EDS-mapping; see details below. Figure 4 As can be seen, C, N, O, Na and Co elements are evenly distributed in it, indicating that ZIF-67 nanoparticles are uniformly dispersed in the hydrogel under the action of dispersant sodium lignosulfonate, which will be beneficial to the catalytic oxidation reaction.
[0032] Example 2 A method for preparing a ZIF-67@SL catalyst includes the following steps: (1) Weigh 24.0 mmol of 2-methylimidazole and add it dropwise to 6.0 mmol of cobalt ion solution (cobalt chloride) while stirring continuously; the concentration of 2-methylimidazole is 2.4 mmol / mL and the concentration of cobalt ion solution is 0.6 mmol / mL.
[0033] (2) Then add 5 mL of deprotonating agent (triethylamine TEA) to the mixed solution, stir at room temperature for 30 min, and let stand for 24 h; (3) Add 1.6 g monomer acrylamide (AM), 0.082 g crosslinking agent MBA and 0.400 g sodium lignosulfonate (SL) to the above suspension, seal the beaker, preheat and stir in a constant temperature water bath to dissolve, and then sonicate for 20 min to disperse the suspension evenly. (4) Add 0.4 mg of initiator persulfate (KPS) to the above mixture, shake quickly, place in a mold, and carry out free radical polymerization reaction in a constant temperature water bath at 45 °C. After a period of time, ZIF-67 composite sodium lignosulfonate hydrogel catalyst is obtained.
[0034] (5) Finally, wash the product with deionized water and anhydrous ethanol several times. After washing, vacuum dry at 60 °C to constant weight to obtain the product.
[0035] Example 3 A method for preparing ZIF-67@SL, the synthetic route is as follows: Figure 1 This includes the following steps: (1) Weigh 32.0 mmol of 2-methylimidazole and add it dropwise to 8.0 mmol of cobalt ion solution (cobalt nitrate) while stirring continuously; the concentration of 2-methylimidazole is 3.2 mmol / mL and the concentration of cobalt ion solution is 0.8 mmol / mL.
[0036] (2) Then add 5 mL of deprotonating agent (ammonia) to the mixed solution, stir at room temperature for 30 min, and let stand for 24 h; (3) Add 2.4 mg of monomer acrylamide (AM), 0.096 g of crosslinking agent MBA and 0.4 mg of sodium lignosulfonate (SL) to the above suspension, seal the beaker, preheat and stir in a constant temperature water bath to dissolve, and then sonicate for 20 min to disperse the suspension evenly. (4) Add 0.4 mg of initiator persulfate (KPS) to the above mixture, shake quickly, place in a mold, and carry out free radical polymerization reaction in a constant temperature water bath at 45 °C. After a period of time, ZIF-67 composite sodium lignosulfonate hydrogel catalyst is obtained.
[0037] (5) Finally, wash the product with deionized water and anhydrous ethanol several times. After washing, vacuum dry at 60 °C to constant weight to obtain the product.
[0038] Example 4 A method for preparing a ZIF-67@SL catalyst, the synthetic route is as follows: Figure 1 This includes the following steps: (1) Weigh 24.0 mmol of 2-methylimidazole and add it dropwise to 6.0 mmol of cobalt ion solution (cobalt acetate) while stirring continuously; the concentration of 2-methylimidazole is 2.4 mmol / mL and the concentration of cobalt ion solution is 0.6 mmol / mL. (2) Then add 5 mL of deprotonating agent (ammonia) to the mixed solution, stir at room temperature for 30 min, and let stand for 24 h; (3) Add 2.0 mg of monomer acrylamide (AM), 0.096 g of crosslinking agent MBA and 0.4 mg of sodium lignosulfonate (SL) to the above suspension, seal the beaker, preheat and stir in a constant temperature water bath to dissolve, and then sonicate for 20 min to disperse the suspension evenly. (4) Add 0.4 mg of initiator persulfate (KPS) to the above mixture, shake quickly, place in a mold, and carry out free radical polymerization reaction in a constant temperature water bath at 45 °C. After a period of time, ZIF-67 composite sodium lignosulfonate hydrogel catalyst is obtained.
[0039] (5) Finally, wash the product with deionized water and anhydrous ethanol several times. After washing, vacuum dry at 60 °C to constant weight to obtain the product.
[0040] Example 5 A method for preparing a ZIF-67@SL catalyst, the synthetic route is as follows: Figure 1 This includes the following steps: (1) Weigh 32.0 mmol of 2-methylimidazole and add it dropwise to 8.0 mmol of cobalt ion solution (cobalt acetate) while stirring continuously; the concentration of 2-methylimidazole is 3.2 mmol / mL and the concentration of cobalt ion solution is 0.8 mmol / mL.
[0041] (2) Then add 5 mL of deprotonating agent (triethylamine) to the mixed solution, stir at room temperature for 30 min, and let stand for 24 h; The deprotonating agent is either ammonia (NH3·H2O) or triethylamine (TEA).
[0042] (3) Add 2.0 mg of monomer acrylamide (AM), 0.108 g of crosslinking agent MBA and 0.4 mg of sodium lignosulfonate (SL) to the above suspension, seal the beaker, preheat and stir in a constant temperature water bath to dissolve, and then sonicate for 20 min to disperse the suspension evenly. (4) Add 0.4 mg of initiator persulfate (KPS) to the above mixture, shake quickly, place in a mold, and carry out free radical polymerization reaction in a constant temperature water bath at 45 °C. After a period of time, ZIF-67 composite sodium lignosulfonate hydrogel catalyst is obtained.
[0043] (5) Finally, wash the product with deionized water and anhydrous ethanol several times. After washing, vacuum dry at 60 °C to constant weight to obtain the product.
[0044] Application testing: To verify the effectiveness of the ZIF-67@SL / PMS catalytic oxidation system, and comparing the degradation effect of ZIF-67@SL prepared in Example 1 on activating other oxidants, the catalytic activity of the material was evaluated by the ratio of naphthalene (NAP) concentration to initial concentration (C / C0) at different time points. Under fixed conditions, 40 mg of ZIF-67@SL was accurately weighed and added to 50 mL of NAP solution (C0 = 10.0 mg·L⁻¹). −1 Subsequently, 50 mg of oxidant was added to the mixed solution to catalyze the oxidation reaction. The oxidants included potassium persulfate (PMS), sodium persulfate (Na₂S₂O₈), potassium persulfate (K₂S₂O₈), ammonium persulfate ((NH₄)₂S₂O₈), peracetic acid (CH₃COOOH), and hydrogen peroxide (H₂O₂). All experiments were conducted in 100 mL water-sealed, stoppered glass conical flasks placed in a 30 °C constant-temperature water bath shaker with the shaker speed adjusted to 150 r / min. After the predetermined time, 500 μL of sample was removed, and saturated ascorbic acid was added to terminate the reaction. The solution was then filtered through a 0.22 μm filter membrane, and the residual NAP concentration in the filtrate was determined by HPLC.
[0045] The results are as follows Figure 5 As shown in the figure, (a) represents the degradation efficiency from 0 to 60 min under different oxidants, and (b) represents the reaction rate constant under different oxidants. ZIF-67@SL's ability to activate Na2S2O8 (PMS) is significantly stronger than other oxidants. The ZIF-67@SL / PMS system achieves a NAP removal capacity of 68.3% with a reaction rate constant of 0.01915 min. -1 .
[0046] To compare the differences in NAP removal efficiency among different reaction systems, the catalytic performance of ZIF-67@SL prepared in Example 1 was tested. The reaction systems included sodium lignosulfonate hydrogel (SL-PAM), ZIF-67, ZIF-67@SL, PMS, SL-PAM / PMS, ZIF-67 / PMS, and ZIF-67@SL / PMS. The catalytic activity of the material was evaluated by the ratio of NAP concentration to initial concentration (C / C0) at different time points. Under fixed conditions, 40 mg of each of SL-PAM, ZIF-67, and ZIF-67@SL (two groups each) were weighed and added to 50 mL of NAP solution (C0 = 10.0 mg·L⁻¹). −1 Six mixed solutions were prepared for later use. Subsequently, 50 mg of PMS was added to a portion of the mixed solutions as needed to form reaction systems of SL-PAM, ZIF-67, ZIF-67@SL, SL-PAM / PMS, ZIF-67 / PMS, and ZIF-67@SL / PMS, respectively. A control group consisting only of PMS was also set up for the reaction. All experiments were conducted in 100 mL water-sealed stoppered glass conical flasks. The conical flasks were placed in a 30 °C constant temperature water bath shaker, and the shaker speed was adjusted to 150 r / min. The water temperature was set according to the experimental conditions. After the predetermined time was reached, 500 μL of sample was taken out and saturated ascorbic acid was added to terminate the reaction. The solution was then filtered through a 0.22 μm filter membrane, and the concentration of residual NAP in the filtrate was determined by HPLC.
[0047] The results are as follows Figure 6 As shown in the figure, the study found that PMS alone also has the ability to degrade NAP, with a removal rate of 18.84%. SL-PAM, ZIF-67, and ZIF-67@SL alone showed very poor removal rates for NAP, failing to degrade it, indicating that the adsorption effect alone is negligible. Furthermore, the figure shows that SL-PAM cannot activate PMS, while the ZIF-67 / PMS system has a good removal effect on NAP, even showing a higher initial catalytic rate than ZIF-67@SL / PMS. At 60 min, the removal efficiencies of both systems are the same. This is mainly because powdered ZIF-67 has a highly efficient catalytic function for PMS, but ZIF-67 is difficult to recycle. The blocky solid structure and easy recyclability of ZIF-67@SL ensure its convenience in practical operation.
[0048] Example 6 To further verify the effectiveness and adaptability of the ZIF-67@SL / PMS system, the ZIF-67@SL catalysts prepared in Examples 1 to 5 were combined with PMS to form catalytic oxidation systems. The degradation effects on other single PAHs [acenaphthene (ACN), dihydroacenaphthene (ACT), fluorene (FLU), and phenanthrene (PHE)] and PAHs with equal volumes of two components were studied, as shown in Table 1 below.
[0049] Table 1. The degradation effect of ZIF-67@SL / PMS system on other PAHs and two-component mixed PAHs
[0050] The results showed that the catalytic oxidation system composed of catalyst ZIF-67@SL and PMS synthesized under different conditions had excellent degradation and removal effects on single PAHs (CAN, ACT, FLU and PHE) other than NAP and PAHs mixed in equal volumes of two components, indicating that the catalytic oxidation system composed of catalyst ZIF-67@SL and PMS has a wide range of adaptability and good effect.
[0051] Example 7: Study on factors affecting the catalytic performance of ZIF-67@SL 7-1. This invention also investigated the effect of sodium lignosulfonate concentration on the catalytic performance of ZIF-67@SL. In the specific preparation, the reaction temperature was 45℃, the dosage of KPS was 10 mg / mL, and Co... 2+ The ratio of SL to 2-methylimidazole was 1:4, and the TEA content was 12.5% (v / v). Five catalysts were prepared by setting five levels of SL concentrations of 2.5, 5, 10, 15, and 20 mg / mL. Figure 7 (a) This shows the effect of different concentrations of SL on the catalytic performance of ZIF-67@SL in the oxidation of naphthalene by PMS. When synthesizing catalyst ZIF-67@SL, except that the SL concentration was set at five levels (2.5, 5, 10, 15, and 20 mg / mL), all other conditions were the same as in Example 1, resulting in five different SL concentrations of ZIF-67@SL. 40 mg of each concentration was added to 50 mL of NAP solution (CO = 10.0 mg·L⁻¹). −1 The reaction was carried out in 100 mL water-sealed, stoppered glass conical flasks. The flasks were placed in a 30 °C constant-temperature water bath shaker, and the shaker speed was adjusted to 150 r / min. The water temperature was set according to the experimental conditions. After the predetermined time was reached, 500 μL of sample was taken out, and saturated ascorbic acid was added to terminate the reaction. The mixture was then filtered through a 0.22 μm filter membrane, and the concentration of residual NAP in the filtrate was determined by HPLC.
[0052] The results showed that the removal rate of naphthalene by ZIF-67@SL gradually increased with increasing SL concentration, reaching a maximum of 53.44% when SL was 10 mg / mL. The study found that the SL structure is rich in oxygen-containing functional groups such as methoxy, carboxyl, carbonyl, and hydroxyl groups. These functional groups capture metal ions to prepare heterogeneous catalysts through ion exchange, electrostatic complexation, or physical adsorption. Therefore, adding SL to the hydrogel is beneficial for increasing its loading capacity of MOF nanoparticles. Furthermore, SL is an excellent anionic surfactant and can also act as a dispersant. SL in the hydrogel maintains the stability of ZIF-67 and enhances its dispersibility in the hydrogel. However, with further increases in SL concentration, the removal rate of naphthalene by ZIF-67@SL significantly decreased. This may be related to the decrease in the relative content of ZIF-67 per unit mass of ZIF-67@SL, leading to a reduction in active sites. Therefore, an SL concentration of 10 mg / mL was selected as the optimal condition for subsequent experiments.
[0053] 7-2. Effect of the mass ratio of SL to AM on the catalytic performance of ZIF-67@SL The reaction temperature was set at 45℃, the dosage of KPS was 10 mg / mL, the dosage of SL was 10 mg / mL, and the mass ratio of SL to AM was set at 1:3, 1:4, 1:5, 1:6, and 1:7 (i.e., AM concentrations of 30, 40, 50, 60, and 70 mg / mL). Figure 7 (b) shows the effect of different SL:AM on the catalytic oxidation performance of NAP by ZIF-67@SL.
[0054] The results showed that as the mass ratio of SL to AM decreased from 1:3 to 1:5, the removal rate of naphthalene by ZIF-67@SL increased from 42.58% to 63.21%. Further increasing the proportion of AM slightly decreased the removal rate. As the matrix material of the hydrogel, a low proportion of AM results in a low cross-linking grafting rate with MBA, leading to a softer network structure and reduced loading capacity for ZIF-67 nanoparticles. Simultaneously, the carboxyl groups of AM have a coordination effect with metal ions, and a low AM content also affects the ZIF-67 loading capacity of the hydrogel. Furthermore, a higher AM proportion enhances the mechanical properties and stability of the hydrogel, improving its resistance to hydraulic shock loads. However, further increasing the amount of AM not only reduces the relative ZIF-67 content per unit mass of ZIF-67@SL, decreasing the number of active sites and lowering the catalytic efficiency of ZIF-67@SL, but also increases the synthesis cost. Considering both degradation rate and cost, a mass ratio of SL to AM of 1:5 (AM concentration of 50 mg / mL) was selected as the optimal mass percentage for the next stage of experiments.
[0055] 7-3. Effect of MBA concentration on the catalytic performance of ZIF-67@SL The reaction temperature was set at 45℃, the dosage of KPS was 10 mg / mL, the dosage of SL was 10 mg / mL, and the SL:AM ratio was 1:5 (AM concentration was 50 mg / mL). Other synthesis conditions were the same as in Example 7-1. Five catalysts, ZIF-67@SL, were prepared by varying the concentration of MBA to 1.8, 2.1, 2.4, 2.7, and 3.0 mg / mL. These five catalysts, synthesized at different MBA concentrations, were then combined with PMS to form catalytic oxidation systems. Experimental studies were conducted on the removal of NAP using the ZIF-67@SL / PMS system. All other experimental conditions were the same as in Example 7-1.
[0056] Figure 7 (c) shows the effect of different MBA concentrations on the catalytic oxidation performance of NAP by ZIF-67@SL. The experiment found that as the MBA concentration increased from 1.8 mg / mL to 3.0 mg / mL, the catalytic oxidation of naphthalene by the synthesized catalyst showed an increasing trend, with the removal rate increasing from 32.84% to 65.46%, while the mechanical strength of the hydrogel also improved. As a crosslinking agent in the hydrogel, insufficient MBA resulted in poor crosslinking, an unstable network structure, a viscous texture, poor mechanical properties, low elasticity, and an inability to stably support ZIF-67 nanoparticles. At concentrations less than 1.8 mg / mL, a gel structure could not even be formed. When the MBA concentration was greater than 2.4 mg / mL, the NAP removal rate stabilized, and the hydrogel structure gradually became denser, reducing its internal pore size and decreasing its swelling performance, which was detrimental to the participation of the active sites within the catalyst in the reaction. Therefore, an MBA concentration of 2.4 mg / mL was selected as the optimal condition for subsequent experiments.
[0057] 7-4. Effect of the molar concentration of Co(NO3)2∙6H2O on the catalytic performance of ZIF-67@SL This invention controls Co during the synthesis of ZIF-67 in an aqueous phase. 2+The molar ratio of ZIF-67 to 2-methylimidazole was 1:4, with 5 ml of TEA and 20 ml of water. In the synthesis experiment of ZIF-67@SL, the amount of ZIF-67 in the lignin-based hydrogel was mainly controlled by adjusting the molar concentration of Co(NO3)2·6H2O. The reaction temperature was set at 45℃, the dosage of KPS was 10 mg / mL, the dosage of SL was 10 mg / mL, the SL:AM ratio was 1:5, the MBA concentration was 2.4 mg / mL, and five gradients of Co(NO3)2·6H2O molar concentrations of 0.025, 0.05, 0.10, 0.15, and 0.20 mmol / mL were set to prepare the catalyst ZIF-67@SL. The catalysts ZIF-67@SL synthesized at these five different Co(NO3)2·6H2O concentrations were selected and combined with PMS to form catalytic oxidation systems. The removal of NAP by the ZIF-67@SL / PMS system was studied. All other experimental conditions were the same as in Example 7-1. Figure 7 (d) shows the effect of different Co(NO3)2·6H2O concentrations on the catalytic oxidation performance of NAP by ZIF-67@SL.
[0058] The results showed that the higher the molar concentration of Co(NO3)2·6H2O, the better and more significant the catalytic oxidation effect of ZIF-67@SL, with the NAP removal rate increasing from 53.68% to 83.77%. ZIF-67, synthesized from Co(NO3)2·6H2O, possesses excellent activation properties for persulfate. The catalytic oxidation performance of ZIF-67@SL mainly depends on the exposed active sites of ZIF-67; therefore, the higher the relative content of ZIF-67 per unit mass of ZIF-67@SL, the better the activation performance. When the molar concentration of Co(NO3)2·6H2O increased from 0.15 mmol / mL to 0.20 mmol / mL, the NAP removal rate increased from 81.47% to 83.77%, an increase of only 2.3%, which was relatively small. This is mainly because the lignin hydrogel itself reached its limit in terms of ZIF-67 loading, the exposure of active sites reached saturation, and the catalytic effect reached its optimal level. From a cost perspective, ZIF-67@SL with a Co(NO3)2·6H2O molar concentration of 0.15 mmol / mL is far more economical than ZIF-67@SL with a molar concentration of 0.20 mmol / mL. Considering both degradation rate and cost, a Co(NO3)2·6H2O molar concentration of 0.15 mmol / mL is selected as the optimal synthesis condition for ZIF-67@SL.
[0059] Example 8 In the preparation of ZIF-67, when the ratio of cobalt ions to 2-methylimidazole is 1:32 and the cobalt salt is cobalt nitrate, ZIF-67 with small and standard crystal size can be synthesized in an aqueous medium at room temperature. However, an excessively high proportion of 2-methylimidazole increases the economic cost of synthesis and makes industrial-scale synthesis difficult. To reduce the proportion of 2-methylimidazole, this invention adds a certain amount of NH3·H2O or TEA organic base during the ZIF-67 preparation process.
[0060] XRD patterns of products prepared using different deprotonating agents are shown below. Figure 8 , where Co 2+ When the molar ratio of NH3 to 2-methylimidazole was 1:2, the product with 5 mL of NH3·H2O added showed almost no diffraction peaks, while the product with 5 mL of TEA added showed obvious diffraction peaks that matched those of the ZIF-67 standard. Figure 9 SEM images of (a) 1:2 NH3·H2O; (b) 1:4 NH3·H2O; (c) 1:2 TEA; (d) 1:4 TEA show that when the molar ratio is 1:2, the product with 5 mL of NH3·H2O added has virtually no fixed crystal structure, with complex and large particles; the product with 5 mL of TEA has obvious crystals, appearing as uneven rhombic dodecahedrons, but it differs significantly from the standard and has a lower yield. When Co 2+ When the molar ratio of NH3 to 2-methylimidazole was 1:4, the product with added 5 mL of NH3·H2O showed obvious diffraction peaks, and the diffraction peaks were disordered, including diffraction peaks of ZIF-67 standard; the product with added 5 mL of LTEA showed obvious diffraction peaks with high matching degree, and the diffraction peak intensity was higher than that of the product with a molar ratio of 1:2. Figure 9 As observed, at a molar ratio of 1:4, the product with the addition of 5 mL of NH3·H2O not only exhibited cross-shaped rod-like crystals but also standard rhombic dodecahedral crystals; the product with the addition of 5 mL of TEA mainly consisted of standard rhombic dodecahedral crystals, consistent with current experimental expectations. Adding different types of deprotonating agents results in products with different microstructures. The addition of TEA can... 2+ ZIF-67 was synthesized when the molar ratio of 2-methylimidazole was 1:2, but ZIF-67 could not be completely synthesized when NH3·H2O was added at a molar ratio of 1:4.
[0061] The above embodiments are merely preferred technical solutions of the present invention and should not be considered as limitations on the present invention. The embodiments and features described in these embodiments can be arbitrarily combined without conflict. The scope of protection of the present invention should be limited to the technical solutions described in the claims, including equivalent substitutions of the technical features described in the claims. That is, equivalent substitutions and improvements within this scope are also within the scope of protection of the present invention.
Claims
1. The application of a ZIF-67 composite sodium lignosulfonate hydrogel catalyst in the catalytic degradation of polycyclic aromatic hydrocarbons by activating potassium persulfate, characterized in that, The catalyst was prepared by the following method: S1. Add the aqueous solution of 2-methylimidazole dropwise to the aqueous solution of cobalt ions and mix thoroughly. The amount of cobalt ions added to the aqueous solution of cobalt ions is 0.10~0.20 mmol / mL, and the molar ratio of cobalt ions to 2-methylimidazole is 1:2~32. Then add ammonia or triethylamine as a deprotonating agent and mix thoroughly. The amount added is 4.0%~20% v / v of the mixed solution. Then, age the solution. S2. Add the monomer acrylamide, the crosslinking agent N,N'-methylenebisacrylamide, and sodium lignosulfonate to the mixed solution obtained in S1, preheat and stir until homogeneous; the amount of monomer added is 40~60 mg / mL, the amount of crosslinking agent added is 2.1~2.7 mg / mL, and the amount of sodium lignosulfonate added is 2.5~10 mg / mL. S3. Add potassium persulfate to the mixture obtained in S2, mix well and react, then wash and dry to obtain ZIF-67 composite sodium lignosulfonate hydrogel catalyst.
2. The application according to claim 1, characterized in that: Cobalt ions can be derived from any one of cobalt acetate, cobalt sulfate, cobalt chloride, or cobalt nitrate.
3. The application according to claim 1, characterized in that: The preheating temperature in S2 is 35-50 ℃.
4. The application according to claim 1, characterized in that: The amount of potassium persulfate added in S3 is 5.0 mg / mL to 11.5 mg / mL.
5. The application according to claim 1, characterized in that: The reaction time in S3 is 3-10 min, the temperature is 40-50℃, after the reaction is complete, it is washed with deionized water and anhydrous ethanol, and finally dried under vacuum at 60℃ to obtain the final product.
Citation Information
Patent Citations
Metal organic framework (MOF) composite materials, methods, and uses thereof
US20200197901A1